Evaluation of ecological carrying capacity and construction of ecological security pattern in West Liaohe River Basin of China - Zheng, Ying; Tang, Pengcheng; Dong, Lei; Yao, Zhenyu; Guo, Jianying (Frontiers in Ecology and Evolution, 2024)
The West Liaohe River Basin (WRLB) is a typical agro-pastoral interlaced zone in Northeast China where excessive economic development activities brought great pressure on the ecosystem and caused a series of ecological problems, having a negative effect on regional ecological carrying capacity (ECC). The rational construction of ecological security pattern (ESP) is an effective way to improve regional ECC and alleviate the contradiction between ecological protection and economic development. In this study, taking the WLRB as an example, spatiotemporal changes of ECC in the WLRB from 2000 to 2020 were explored by using spatial principal component analysis (SPCA). Furthermore, ecological sources were determined by coupling ECC evaluation results with important ecological patches such as natural protected areas, and the minimum cumulative resistance (MCR) model combined with the circuit theory method were employed to identify ecological security zoning, ecological corridors and key ecological nodes. Then a comprehensive ESP of the basin was constructed. The results show as follows: 1) The ECC of the overall WLRB was at medium carrying level, yet was spatially differentiated, which decreased from the periphery to the center of the basin in general. ECC showed a fluctuating upward trend from 2000 to 2020. 2) The ecological source area of the WLRB was 21926.91 km² , accounting for 17.33% of the total study area. The ecological sources were seriously fragmentated and mainly distributed in the mountain area. The area of ecological conservation zone, optimized buffer zone, ecological transition zone, ecological prevention and control zone were 55672.69 km² , 32662.24 km² , 23862.84 km² and 12021.04 km² , accounting for 44.82%, 26.29%, 19.21% and 9.68%, respectively. We also extracted 95 ecological corridors (with a total length of 3130.97 km), 49 ecological pinch points (with a total area of 200.33 km²) and 30 ecological barrier points (with a total area of 318.30 km²), constituting a "points-linesplanes" comprehensive ecological security pattern. This research can provide scientific reference for the protection and restoration of ecological environment and regional sustainable development.